Пищевой и технический казеин: способы использования - Богосян, М.В. (Культура народов Причерноморья, 2014)
В статье рассмотрены вопросы возможного дальнейшего использования как пищевого, так и
технического казеина. Предложены пути использования пищевого казеина при производстве хлебобулочных
продуктов, напитков, модифицированных молочных продуктов, также в мясной, кондитерской,
фармацевтической и медицинской промышленности. Освещен ряд производств с использованием
технического казеина, а именно: производство пластика, резиновых изделий, красок, грунтовок, мелованной
бумаги и картона, использование в деревообрабатывающей и кожевенной промышленности. У статті розглянуті питання можливого подальшого використання як харчового, так і
технічного казеїну. Запропоновано шляхи використання харчового казеїну при виробництві хлібобулочних
продуктів, напоїв, модифікованих молочних продуктів, також у м'ясній, кондитерській, фармацевтичної і
медичної промисловості. Висвітлено низку виробництв з використанням технічного казеїну, а саме:
виробництво пластика, гумових виробів, фарб, ґрунтовок, паперу і картону, використання у деревообробній і
шкіряної промисловості. Questions of possible use of the food and technical casein consideration of articles. The ways of using
edible casein in the manufacture of bakery products to increase the viscosity of flour, in the beverage industry - as
stabilizers in the production of modified dairy protein to saturate and improve product quality in the meat industry in
the production of meat substitutes, in the confectionery industry to impart elasticity caramel, in the pharmaceutical and
medical industry in the manufacture of a dietary product. It highlighted a number of production using a commercial
casein, namely the production of plastic, rubber, paints, coatings, coated paper and paperboard use in the wood
industry for gluing of wood articles, in the leather industry to enhance the strength of the skin.